ARTIFICIAL INTELLIGENCE AND THE FUTURE OF ISLAMIC EDUCATION: OPPORTUNITIES, CHALLENGES, AND ETHICAL IMPLICATIONS - Nita Lustia; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The technological revolution driven by artificial intelligence (AI) has penetrated the realm of education, including Islamic educational institutions, presenting both strategic opportunities and multifaceted challenges that demand value-based responses grounded in Islamic principles. This study aims to map the strategic potential of AI, analyze barriers to its integration, and formulate an ethical framework based on maqāṣid al-syarī'ah and the concept of maṣlaḥah as normative guidance for responsible technology utilization in Islamic education. This research employs a qualitative approach through library research design, utilizing descriptive-interpretive content analysis of reputable academic sources published between 2021 and 2025. Findings reveal that AI offers significant potential for personalized learning, institutional administrative efficiency, and broader access to value-based Islamic education. Nevertheless, persistent challenges including digital infrastructure disparities, insufficient technological literacy among educators, and the threat of algorithmic bias remain considerable obstacles that require systematic resolution. From an ethical standpoint, AI utilization demands a robust normative foundation to prevent technology from displacing the spiritual values and character development that are central to Islamic education. This study concludes that AI integration must be implemented responsibly, strategically, and in alignment with the holistic objectives of Islamic education, ultimately nurturing a generation of Muslims who excel intellectually while remaining firmly grounded in spirituality and morality.